An Analysis of Slang Words Used in Rich Brian’s Song “Getcho Mans” - I Komang Krisna Surya Patanjali; I Komang Sulatra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research purpose is to acknowledge types of slang words used in a song. The descriptive qualitative method is utilized in this research to gather and analyse the data from the song lyrics. The data source is a song by Rich Brian entitled “Getcho Mans”. Theory of Allan & Burridge about the type of slang words is utilized to analyse the data. This study successfully classified the slang words used in “Getcho Mans” by Rich Brian. This study found that song by Rich Brian entitled “Getcho Mans” contained slang words in the types of Fresh & Creative, Flippant, Imitative, and Clipping. The writer could not find acronym type of slang words in this song. The total of 47 pieces of data collected from the analysis. The findings could help English students to understand the type and the example of words that usually appear in Hip-Hop songs. Furthermore, it could help the readers to understand the meaning of slang words that usually utilized by Rappers.